Pengaruh Lingkungan Kerja Terhadap Kinerja Karyawan Unit Export Final Product Pada PT. Aneka Bumi Pratama Palembang - Imam Suroso; Vivin Afini; Aras Tulip; Tutik Pebrianti; Indah Mawarni (JURNAL EKOBIS Kajian Ekonomi dan Bisnis, 2018)
ABSTRACT This study aims to analyze the influence of the work environment (physical and non-physical) on the performance of employees in the Final Product Export Unitat PT Aneka Bumi Pratama Palembang.The type of data in this studyis primary data collected by the question naire instrument. The sampling techniquein this study uses saturated samples. Multipleregression analysis was used totes tthe hypothesis in this study.Theresults ofthestudy at the 5% significance levelfound that: (1) thephysical workenvironment had no effect on the performance of the employees of the Export Final Productunitat PT. Aneka Bumi Pratama, the data obtained that t count of 2.215 is greater than ttable(n=20,α=5%) of 1.736, the significance valueisgreater than the alpha value (0.324 > 0.05). (2) non-physical work environment doesnot affect the performance of the Export Final Product unit at PT. Aneka Bumi Pratama, the data obtained t hat calculated t2.457 is greater than t table (n =20,α=5%) of the significance valueis greater than alpha (0.654<0.05). (3) Work environment and non-physical work environment variables have no effect on employee performance,obtained data that the significance value of 0.603 is greater than the alphavalue(α)= 0.05(0.603> 0.05). It is suspected that there are other ariables outside the model that have further influence to the performance of the employees of the Export Final Product Unit at PT. Aneka Bumi Pratama Palembang.